2006
DOI: 10.1103/physrevd.74.015005
|View full text |Cite
|
Sign up to set email alerts
|

Linear confinement and AdS/QCD

Abstract: In a theory with linear confinement, such as QCD, the masses squared m 2 n,S of mesons with high spin S or high radial excitation number n are expected, from semiclassical arguments, to grow linearly with S and n. We show that this behavior can be reproduced within a putative 5-dimensional theory holographically dual to QCD (AdS/QCD). With the assumption that such a dual theory exists and describes highly excited mesons as well, we show that asymptotically linear m 2 spectrum translates into a strong constrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
2,165
7
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,098 publications
(2,252 citation statements)
references
References 34 publications
56
2,165
7
14
Order By: Relevance
“…As for the resonances, in [22] it was shown that one can get linear confinement by including a quadratic dilaton Φ ∼ z 2 in the pure AdS background (see also [26] for a phenomenological treatment including a UV cutoff). The peculiar z 2 dependence of the dilaton is far from clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the resonances, in [22] it was shown that one can get linear confinement by including a quadratic dilaton Φ ∼ z 2 in the pure AdS background (see also [26] for a phenomenological treatment including a UV cutoff). The peculiar z 2 dependence of the dilaton is far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed we will show that this can be done consistently while finding the back-reaction on the geometry. The second option may have significant implications in the context of linear confinement where a specific IR behavior for the metric and dilaton have been discussed in [22]. Finding a back-reacted solution which gives this is an important goal and is discussed more in section 4.…”
Section: The Phenomenological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In [265] it was pointed out though that if the dilaton grows as 1 r 2 in the IR the potential V will be of the form…”
Section: Regge Behaviour and The Soft Wallmentioning
confidence: 99%
“…by deriving holographic QCD from string theory [23][24][25][26], and bottom-up approach, i.e. by examining holographic QCD from experimental data and lattice results [16,[27][28][29][30][31].…”
Section: Deformed Ads Backgroundsmentioning
confidence: 99%